Il trattamento di pazienti con sepsi grave mediante drotrecogin alfa: una valutazione economica con riferimento all’Italia - Lucioni, Carlo; Mazzi, Silvio; Christopher, Chinn (Farmeconomia. Health economics and therapeutic pathways, 2002)
Sepsis can be defined as a spectrum of clinical conditions caused by the immune response of a host to infection or trauma and characterized by systemic inflammation and coagulation. Particularly in elderly, immunocompromised and critically ill patients, sepsis is a major cause of morbidity and mortality in intensive care units (ICUs) worldwide. In the US, sepsis is the leading cause of death in noncoronary ICU patients. Drotrecogin alfa, or recombinant human activated protein C, has antithrombotic, antiinflammatory, and profibrinolytic properties. Recently in a phase III trial (PROWESS), Drotrecogin alfa demonstrated significantly reduced mortality in severe sepsis patients at 28 days. In this trial important value factors for the assessment of costs and outcomes of severe sepsis were also considered. The purpose of the present study is to determine the economic burden of the treatment with Drotrecogin alfa, according to a cost-effectiveness analysis based on the data of the PROWESS trial. The study has been adapted to the italian health environment. As regards to the costs per surviving patient and costs per QALY (Quality Adjusted Life Year), the predicted cost-effectiveness ratio of drotrecogin alfa in severe sepsis patients is much lower than the standard values considered as acceptable in the international litterature.